Adapting the WTO trade policy reviews to the need of developing countries: Starting points and options - Axel Borrmann; Georg Koopmann (Hamburg Institute of International Economics (HWWA), 2002)
For decades now, trade assistance has been one of the traditional components in Germany's programme of development cooperation (DC) (see section 2.4). On a multilateral level, support has been provided to the World Trade Organization (WTO), the International Trade Centre (ITC) and the Joint Integrated Technical Assistance Programme (JITAP). The background to this study is the contribution Germany made to the WTO's Global Trust Fund in January 2000 to promote further development and adaptation of the Trade Policy Review Mechanism (TPRM) to the needs of developing countries, and especially those of the Least Developed Countries (LDCs) (see Appendix 4). The Federal Ministry for Economic Cooperation and Development (or BMZ, short for Bundesministerium für wirtschaftliche Zusammenarbeit und Entwicklung) has asked the Hamburg Institute of International Economics (HWWA) to carry out a brief study designed to identify starting points for this adaptation process and consider the options available.
Keywords: 330